2021
DOI: 10.3390/nu13113846
|View full text |Cite
|
Sign up to set email alerts
|

Time-Restricted Feeding in Mice Prevents the Disruption of the Peripheral Circadian Clocks and Its Metabolic Impact during Chronic Jetlag

Abstract: We used time-restricted feeding (TRF) to investigate whether microbial metabolites and the hunger hormone ghrelin can become the dominant entraining factor during chronic jetlag to prevent disruption of the master and peripheral clocks, in order to promote health. Therefore, hypothalamic clock gene and Agrp/Npy mRNA expression were measured in mice that were either chronically jetlagged and fed ad libitum, jetlagged and fed a TRF diet, or not jetlagged and fed a TRF diet. Fecal short-chain fatty acid (SCFA) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Further, we have previously shown that restoration of the rhythm in the food intake pattern using night-time restricted feeding in mice during chronic jetlag can prevent the effect of chronodisruption on gut epithelial homeostasis. 43,44 This may provide a rationale for the beneficial effects observed with intermittent fasting which is gaining in popularity as a nutritional approach to combat the metabolic syndrome in chronodisrupted obese patients. 45,46 We believe that shift workers may benefit from a similar approach to prevent gastrointestinal symptoms since their window of caloric intake is often stretched over nearly the entire day.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have previously shown that restoration of the rhythm in the food intake pattern using night-time restricted feeding in mice during chronic jetlag can prevent the effect of chronodisruption on gut epithelial homeostasis. 43,44 This may provide a rationale for the beneficial effects observed with intermittent fasting which is gaining in popularity as a nutritional approach to combat the metabolic syndrome in chronodisrupted obese patients. 45,46 We believe that shift workers may benefit from a similar approach to prevent gastrointestinal symptoms since their window of caloric intake is often stretched over nearly the entire day.…”
Section: Discussionmentioning
confidence: 99%
“…Desmet et al. 322 demonstrated that TRF selectively prevents jet lag‐induced disruption of the central biological clock in mice and regulates the normal rhythm of food intake to prevent weight gain. This suggests that proper feeding/fasting cycles can coordinate or reshape the biological clock to regulate behavioral and metabolic rhythms.…”
Section: Potential Mechanism Mediating the Effects Of Dietary Patternsmentioning
confidence: 99%
“…319,320 For example, Chaix et al 321 demonstrated that TRF effectively ameliorated metabolic defects in Cry1;Cry2 (CDKO) and liver-specific Bmal1 and Rev-erbα/β-knockout mice, thereby preserving circadian rhythms in liver transcripts and nutrient-sensing pathways. Desmet et al 322 demonstrated that TRF selectively prevents jet lag-induced disruption of the central biological clock in mice and regulates the normal rhythm of food intake to prevent weight gain. This suggests that proper feeding/fasting cycles can coordinate or reshape the biological clock to regulate behavioral and metabolic rhythms.…”
Section: Circadian Rhythmsmentioning
confidence: 99%
“…On the molecular level the circadian clock consist of core clock genes forming an autoregulatory transcriptional-translational feedback loop, thereby driving circadian oscillations of genes involved in various pathways (Takahashi, 2017). While the central clock in the hypothalamus is mainly entrained by light, peripheral clocks, including pancreas, liver, adipose tissue and the gastrointestinal (GI) tract, are predominantly entrained by the timing and composition of nutrient intake (Damiola et al, 2000;Desmet et al, 2021;Pickel and Sung, 2020). These metabolic relevant organs are responsible for digestion, absorption as well as nutrient utilization in a circadian manner (Pickel and Sung, 2020).…”
Section: Introductionmentioning
confidence: 99%